Reclaiming public spaces: Radical alternatives to the exclusionary project of rightsizing policies - Luisa Rossini (PlaNext)
Under the growing pressure of financial markets, the shrinking of public resources and services have been justified by discourses on inefficiency or redundancy in cities adhering to a dominant growth paradigm in urban development and planning, within the framework of austerity policies. Related rightsizing policies are then identifiable as forms of smart shrinkage and can be described as exclusionary projects in a context of increasing social polarisation. In response to these developments, groups of inhabitants have begun employing reclaiming strategies for the co-/self-management of public spaces and services, countering the conversion of common, collective, and state forms of property rights into exclusive private property rights. While these initiatives may, on one hand, be driven by the mainstream rhetoric of the citizen entrepreneurship, social market and “Big Society,” which often align with neoliberal frameworks emphasising privatization and individual responsibility, on the other hand, these forms of “subsidiarity with the state” emerged from a counter rhetoric rooted in solidarity, social sustainability and urban justice. This counter rhetoric advocates for collective, community-driven approaches challenging the logic of privatisation and for more equitable and sustainable planning models. Building on these reflections, the article seeks to analyse a paradigmatic case of resistance against privatization through the creation of a radical alternative social project for the self-management of public spaces and service delivery. By examining the compelling case of the illegal occupations and subsequent legalisations of the former hospital Bethanien in Berlin, the article explores how this experience of self-management demonstrated effective alternatives to the reduction of public spaces through the implementation of bottom-up practices aligned with the principles of degrowth.